Cyclin dependent kinase 9 inhibitor induces transcription-replication conflicts and DNA damage accumulation in breast cancer - Minyoung Lee; Kyung-Hun Lee; Ahrum Min; So Hyeon Kim; Sujin Ham; Hae Min Hwang; Youlim Noh; Yu-Jin Kim; Dae-Won Lee; Jiwon Koh; Seock-Ah Im (Cancer Cell International)
Abstract Background Cyclin-dependent kinase 9 (CDK9) is a crucial regulator of transcriptional progression of RNA polymerase-II (RNAP2). RNA polymerases trapped in DNA can be a source of transcription-replication conflict (T-R conflict), which is a common source of replication stress. AZD4573, a highly selective CDK9 inhibitor, has been shown to induce apoptosis in leukemia cell lines, while its anti-tumor potential in breast cancer has yet to be elucidated. Methods To evaluate the cytotoxicity of AZD4573 in vitro, MTT assays were performed. The expression of signal transduction molecules was determined using Western blotting, immunoprecipitation, and immunofluorescence. Apoptotic cell death was verified by the annexin-V assay. DNA strand breaks and repair efficacy were evaluated through the alkaline comet assay. The siRNA knock-down system was used to confirm the action mechanism. Results AZD4573 induced T-R conflicts during S-phase, increasing replication stress and DNA strand breaks, resulting in apoptosis by induction of caspase-3. Furthermore, we identified Dead-box 25 (DDX25) helicase as a key mediator in resolving the T-R conflicts. Nuclear translocation of DDX25 correlated with reduced sensitivity to AZD4573 by the resolution of T-R conflicts. Conclusions Inhibition of CDK9 by AZD4573 induces the accumulation of DNA damage through T-R conflicts. DDX25 helicases were identified as a key mediator in resolving T-R conflicts and the reduced sensitivity to AZD4573.